Affective dimension of teacher´s pedagogical leadership - Gento Palacios, Samuel; González-Fernández, Raúl; Silfa Sención, Heriberto-Orangel (Revista Complutense de Educación, 2020)
INTRODUCTION. Recent research on the subject indicates that teacher’s leadership is a key element for the improvement of educational quality. To be considered as a true pedagogical leader, the teacher must have some features to define him as such. In this context, the objectives of this research try to identify the relevance of the dimensions that define a teacher as a true leader, as well as determine the importance of the different features that identify the affective or emotional dimension of the same. METHOD. In order to achieve these objectives, descriptive research has been carried out. In its development a quantitative methodology has been used, through the use of a specifically validated questionnaire with sufficient reliability which has been completed by the main stakeholders in the educational activity (n=1116): students, parents, teachers and members of management teams. RESULTS. In the results obtained, the high score given to the affective dimension of the pedagogical leadership of the teacher stands out, followed by the participative and formative dimensions, as well as the different features inherent to them. In both cases there is, in a statistically significant way, a lower assessment obtained from students in relation to the other sectors considered in the research. DISCUSSION. The research carried out demonstrates the importance of affective or emotional dimension of the teacher in the exercise of true pedagogical leadership. Within this dimension, the importance of the courteous and delicate treatment from the teacher towards all the members of the educational institution, as well as the recognition of their dignity as such individuals, stand out.